Premna sebrabergensis (Lamiaceae, Premnoideae), a new species from Angola and Namibia - Swanepoel, Wessel; van Jaarsveld, Ernst J.; Becker, Rolf W.; van Wyk, Abraham E. (Phytotaxa, 2025)
Premna sebrabergensis, hitherto misidentified in herbaria as Volkameria glabra (= Clerodendrum glabrum), is here described as a new species. It is a range-restricted species, only known from the Zebra Mountains in the Kaokoveld Centre of Endemism, in northwestern Namibia and southwestern Angola. It grows primarily in soils derived from anorthosite and gabbro of the Kunene Igneous Complex. Diagnostic characters for P. sebrabergensis include the pale green or yellow-green appearance of the plants, vegetative parts with an indumentum of simple antrorse-directed white trichomes and yellow glandular peltate scales, leaves usually ovate, often with elongated acuminate apex and flowers in paniculately arranged cymes. Based on IUCN Red List criteria, a provisional conservation assessment of Endangered (EN) is recommended for the new species.